Climate systems [electronic resource] : interactive forces of global warming - Casper, Julie Kerr (Global warming, 2009)
A study of global warming, discussing the elements of Earth's climate system, the carbon cycle, plate tectonics, the flow of energy, planetary and global motions in the atmosphere, local motions in the atmosphere, ocean currents, the global warming issue, and what global warming means for the future